Clinico-etiological profile of neonatal sepsis at a tertiary care hospital in South India - Kumar Kamalakannan Santosh (Halo 194, 2022)
Introduction/Objective Neonatal sepsis is the leading cause of morbidity and mortality among neonates. Neonates are at risk of sepsis due to several immaturities that they possess inherently. Sepsis is classified as early-onset or late-onset neonatal sepsis. Pathogenesis is different in both types. This study aims to determine the pattern of microorganisms causing sepsis and the clinical presentation of neonates admitted with suspicion of sepsis to the Government Kilpauk Medical College Hospital, a tertiary medical care centre. Methods Descriptive cross-sectional study performed in Government Kilpauk Medical College and Hospital, India. Results Out of 207 neonates admitted with suspected sepsis, 112 were male and 97 were female. Male to female ratio was 54.1% : 45.9 % (1.2 : 1). On categorizing the newborns based on birth weight, 11 newborns were of very low birth weight, 107 were of low birth weight, 88 had normal birth weight, and one baby weighed more than 4,000 grams. Blood culture was positive in 88 out of the 207 cases (42.51%). Klebsiella was the commonest microorganism causing sepsis (45%) in our Neonatal Intensive Care Unit. Other Gram-negative isolates included Escherichia Coli (31%), Pseudomonas (6%), Enterobacter (1%) and Acinetobacter (2%). The Gram-positive organisms grown were coagulase-positive and coagulase-negative Staphylococci (8%), Group B Beta Hemolytic Streptococcus (5%) and Enterococcus (2%). Late-onset sepsis cases were found to be 1.5 times more common than early-onset sepsis. The best overall sensitivity among Gram-negative isolates was to Imipenem (92%), followed by Amikacin (82.66%) and the best sensitivity among Gram-positive isolates was to Vancomycin (84.61%), followed by Cloxacillin and Ampicillin (61.53%). Out of 88 positive cultures, 6 were multi-drug resistant (6.8%). Conclusion Acquiring knowledge about the microorganisms causing sepsis in neonates helps prevent morbidity, mortality and the development of antibiotic resistance.